Translation technique for translating children’s songs in Cocomelon YouTube channel - Nurdin Bramono; Muhammad Fa'iz Hasan (Pioneer: Journal of Language and Literature, 2026)
Translating children’s songs requires specific techniques to convey the lyrics accurately because of their linguistic features. This study examines translation strategies for four songs on the Cocomelon YouTube channel in Indonesia. The four songs are Twinkle-Twinkle Little Star, The Wheels on the Bus, Sick Song, and Finger Family, as it is a descriptive qualitative study that applied Molina and Albir’s (2002) concept of translation techniques. The result reveals that two variants of the translation technique are found. They are single and couplet techniques. In the single technique, the three most commonly used of the five are adaptation, modulation, and literal. Meanwhile, in the couplet technique, there are eleven found, which are the couple of amplification and reduction translation techniques most commonly used. The strategies found in this study show that the translation technique used contributes to the development of similar language characteristics in children’s songs, in terms of simple language and repetitive words, between the source and target languages.